Effect of Total Taxable Entrepreneurs (PFM), Income Per Capita, Inflation, And Economic Growth of Revenue Service Tax Vat Office Pekanbaru - Alex Sentami Putra; Amir Hasan; Azhari ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of the amount of taxable employers (PFM). This study aimed to examine the effect of the amount of taxable employers (PFM) rate and the rate of economic growth in VAT receipts Pekanbaru city. Data used in this study is a secondary data from BPS data and LTO in Pekanbaru. The method used in this research is the study of time series for 5 years from 2008 to 2012 with monthly data units, the number of samples is 60 pieces. Hypothesis testing is performed by using linear regression analysis based on multiple hypothesis testing. result of this research indicates the amount of taxable employers, income per capita, inflation and economic growth affect the acceptance of Pekanbaru city VAT at 14.3% while the remaining 85.7% is influenced by other variables. The results of hypothesis testing found that inflation does not have a significant impact on VAT receipts Pekanbaru= 0664> 0:05. Meanwhile, the amount of taxable employers (PFM), per capita income and economic growth has a significant influence on VAT receipts Pekanbaru = 0.015 <0.05 0.007 <0.05 0.009 <0.05 level. Keywords: entrepreneur taxable amount (PFM), income per capita, inflation, economic growth, the city of Pekanbaru VAT receipts